The ratio of unemployment rates and fair employment: a reply to John Bradley - Breen, Richard (Economic & Social Studies, 1998)
John Bradley's comments on Evaluation of the Ratio of Unemployment Rates as an Indicator of Fair Employment (Gudgin and Breen, 1996; henceforth G&B) reveal a thoroughgoing confusion about the debate to which the study seeks to contribute, the issue that the report sought to address, and the workings of the model on which our conclusions are based.
Keywords: Unemployment rates; Fair employment; Ireland